Association of NRAMP1 Polymorphisms with Immune Traits in Indonesian Native Chickens - Muhsinin, M.; Ulupi, N.; Gunawan, A.; Wibawan, IWT.; Sumantri , C. (International Journal of Poultry Science, 2016)
Background: Natural resistance-associated macrophage protein-1 gene (NRAMP1) plays an important role in immune response against intracellular pathogens. Objective: This study was aimed at identifying NRAMP1 polymorphisms and their association with immune traits in Indonesian native chickens. Methodology: Genetic polymorphism of chickens was investigated using polymerase chain reaction-restriction fragment polymorphism. The concentrations of leukocytes and differentiation (heterophile, lymphocyte and monocyte) were assessed by the Giemsa method and immune traits were detected by followed clearance test. Results: The results showed that NRAMP1 was polymorphic in all native chickens. The CC genotype was significantly higher than CT and TT genotypes (p<0.05) in Sentul chickens resistant to Salmonella pullorum. Although, the concentrations of leukocytes and differentiation in chickens with all three of NRAMP1 genotypes (CC, CT and TT) were not statistically different, there was a significant correlation between different NRAMP1 genotypes and immune traits. Therfore, NRAMP1 is proposed to be a disease resistance candidate gene. Conclusion: However, this study should be validated in other chicken populations to evaluate the potential exploitation of NRAMP1 in selective breeding.